Fixed-time SOSM controller design subject to an asymmetric output constraint - Wang, Lei; Mei, Keqi; Ding, Shihong (Journal of the Franklin Institute, 2021)
This paper addresses the problem of fixed-time controller design for the second-order sliding mode (SOSM) dynamics with asymmetric output constraints. Based on the construction of a barrier Lyapunov function (BLF) and the technique of adding a power integrator, a fixed-time SOSM controller that can be used to handle the asymmetric output constraint issue is developed. A strict Lyapunov stability analysis shows that the developed SOSM controller guarantees that the sliding variable can converge to the origin within a fixed time that is irrelevant to the system initial conditions. Meanwhile, the system output will never invade the boundary of the preset asymmetric constrained area. Finally, two examples are given to verify the effectiveness and the feasibility of the proposed scheme.